First record of the nudibranch Marionia blainvillea (Risso, 1818) (Gastropoda: Heterobranchia) for Montenegro - Mačić, Vesna (Array, 2018)
One specimen belonging to the nudibranch Marionia blainvillea (Risso, 1818) was found crawling on the gorgonian Leptogorgia sarmentosa (Esper, 1789) at Sv. Nedjelja, Boka Kotorska Bay, Montenegro. This is the first record of the species for Montenegrin waters and the third for the Adriatic Sea.